Management of Pentalogy of Cantrell with complete ectopia cordis and Double Outlet Right Ventricle. (May 2015) - Harring, Gesa; Weil, Jochen; Thiel, Christian; Schmelzle, Rainer; Mueller, Goetz C.
Abstract Pentalogy of Cantrell (PoC) is a rare congenital midline defect. We present a case and its treatment of PoC with complete ectopia cordis and congenital heart disease. Postnatally the congenital heart defect was surgically corrected and the ectopic heart was covered by musculous mobilized flap. Due to cephalic orientation of the heart and limited intrathoracic space, replacement of the heart into the thoracic cavity was initially not performed. After 11 years of follow up our patient now is without relevant limitations solely wearing a thoracic shelter. This case elucidates the complexity of further management. The potential risk of disastrous hemodynamic compromise by intrathoracic shift is to compare with the limited safety of the ectopic heart.